Brazil - Broadening the Base for Growth : A Report on the State of Bahia - World Bank (Washington, DC, 2013)
Over the last thirty years, Bahia has transformed itself from a somnolent rural economy to the leading manufacturing state of the Northeast. In the process, the state government has developed a reputation as a modernizing, fiscally responsible administration. But problems remain. Growth rates, even since the last recession, have been modest. Poverty remains widespread. The aim of this report is to define ways which the state can take to provide the basis for sustained, broad-based economic growth. Overall, the report is optimistic about Bahia's prospects. The economy is increasingly diversified. New entrants to the labor force, while still under-skilled, are better educated than their forebears. The state's strong fiscal condition gives it room to address gaps in social services. But a less capital-biased growth strategy, combined with 1) federal-level reforms in fiscal policy, labor legislation, and pension regulation; and 2) state-level reforms in the management of social services, would enhance the state's growth prospects and hasten the reduction of poverty.